Making Assessment Count: Using Effective Assessment Practices to Reinforce Teaching and Learning Activities - Hartfield, Perry J. (INTI International University, 2011)
This study will investigate how assessment works to frame student learning, and, more precisely, it will examine how effective assessment practices support and reinforce teaching and learning activities. Constructive alignment of teaching and (earning activities and the assessment Items within a teaching unit and, ultimately, a course can work to reinforce the ability of students to achieve superior assessment outcomes and, consequently, enhance student satisfaction with assessment. A high quality assessment framework will depend on these aforementioned characteristics coupled with timely, effective and formative feedback on continuous assessment. This study questions how students engage with their assessment in an interdisciplinary year level biochemistry teaching unit. A series of student surveys and locus group interviews were used Lo explore the quality, quantity and efficacy of the assessment framework. The outcomes from this study indicated that the teaching, (earning and assessment activities within this teaching unit were effectively aligned, and this framework supported and developed student teaming and understanding. Moreover, the evidence suggests that constructive alignment of teaching, teaming and assessment motivates students to achieve quality outcomes with respect to grades through authentic assessment experiences, and leads towards Improved and more effective Learning environments.